2000
DOI: 10.1590/s0006-87052000000100002
|View full text |Cite
|
Sign up to set email alerts
|

Espectro polínico de amostras de mel de Apis mellifera L., coletadas na Bahia

Abstract: RESUMOO espectro polínico encontrado em amostras de mel provenientes de seis municípios do Estado da Bahia foi analisado com o objetivo de contribuir para o conhecimento da flora visitada por Apis mellifera L. 1758 (Hymenoptera: Apidae)A identificação dos tipos polínicos foi feita por meio de literatura especializada e de informações de campo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
23

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 9 publications
1
17
0
23
Order By: Relevance
“…and Mimosa spp. types were also remarked by Barth (1989), Durán et al (1996) and Moreti et al (1998) in samples of Apis mellifera honey coming from Bahia. In spite of the Eucalyptus spp.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…and Mimosa spp. types were also remarked by Barth (1989), Durán et al (1996) and Moreti et al (1998) in samples of Apis mellifera honey coming from Bahia. In spite of the Eucalyptus spp.…”
Section: Resultssupporting
confidence: 52%
“…In spite of the Eucalyptus spp. type having been considered by Barth (1989), just as SP, it was observed that these species are found as DP in the samples of A. mellifera honey in different regions in the State of Bahia, principally due to the increase of reforested areas with this vegetable species in the latest years (Moreti et al, 1998).…”
Section: Resultsmentioning
confidence: 86%
“…A identifi cação dos tipos polínicos foi realizada por comparação com lâminas de referência, além da utilização de material especializado (Mendonça et al 2008;Luz et al 2007;Roubik & Patiño 2003;Moreti et al 2000;Oliveira et al 1998;Barth et al 1998). Assim, foi dada atenção às espécies botânicas coletadas na área que se correlacionavam com as lâminas de mel e pólen.…”
Section: Methodsunclassified
“…Nos outros meses do estudo este tipo polínico foi classifi cado como pólen isolado (PI). O pólen de M. caesalpiniifolia também foi observado por Moreti et al (2000) em análises de amostras de mel no município de Rio Real (BA).…”
Section: Fatores Ambientais (Precipitação E Temperatura) E Recurso Flunclassified
“…The knowledge of the food sources most employed by bees is important to define strategies to enhance beekeeping productivity and profitability, as well as to certify the good quality and provenance of honeys (Bastos, 1996;Moreti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%